Evolution of macroscopic elastic moduli of martensitic polycrystalline NiTi and NiTiCu shape memory alloys with pseudoplastic straining. (15th January 2017) - Thomasová, Martina; Seiner, Hanuš; Sedlák, Petr; Frost, Miroslav; Ševčík, Martin; Szurman, Ivo; Kocich, Radim; Drahokoupil, Jan; Šittner, Petr; Landa, Michal
Abstract: Elastic constants of polycrystalline NiTi and NiTiCu shape memory alloys in the martensite phase were determined by resonant ultrasound spectroscopy; the evolution of these constants was studied with subsequent applications of compressive loads inducing reorientation of martensitic variants. While the initial thermally-induced martensite exhibited only weak elastic anisotropy resulting from the underlying crystallographic texture of the parent phase, the materials with oriented martensitic microstructures exhibited strong elastic anisotropy with Young's moduli in different directions differing by several tens of GPa−s. A qualitative difference in behaviors was observed between the monoclinic B19′ martensite in the NiTi alloy and the orthorhombic B19 martensite in the NiTiCu alloy. Graphical abstract: Image 1